2015
DOI: 10.1039/c4ra15643a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable luminescence properties of the novel Tm3+- and Dy3+-codoped LiLa(MoO4)x(WO4)2−x phosphors for white light-emitting diodes

Abstract: A series of Tm 3+ -and Dy 3+ -codoped LiLa(MoO 4 ) X (WO 4 ) 2-X phosphors were prepared via the conventional solid-state reaction method. It was discovered that both the optimum single doped concentration of Tm 3+ and Dy 3+ are 0.04 for LiLa(WO 4 ) 2 host, LiLa(WO 4 ) 2 :0.04Tm 3+ and LiLa(WO 4 ) 2 :0.04Dy 3+ will emit blue and yellow light, respectively. On the other hand, the emission colors of Tm 3+ -and Dy 3+ -codoped LiLa(WO 4 ) 2 could be tuned from blue to white through tuning the 10 energy transfer. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…can be seen that the central W 6+ is coordinated by four oxygen atoms at a tetrahedral site and the Li + and Gd 3+ cations are randomly distributed over the same site positions and are coordinated by eight oxygen atoms to form a distorted polyhedron with symmetry S 4 (without an inversion center). [29][30][31] Based on the similar effective ionic radii and charge balance, the Tm 3+ , Tb 3+ , Dy 3+ and Eu 3+ ions are expected to occupy Gd 3+ sites in LiGd(WO 4 ) 2 .…”
Section: Phase Identication and Structurementioning
confidence: 99%
“…can be seen that the central W 6+ is coordinated by four oxygen atoms at a tetrahedral site and the Li + and Gd 3+ cations are randomly distributed over the same site positions and are coordinated by eight oxygen atoms to form a distorted polyhedron with symmetry S 4 (without an inversion center). [29][30][31] Based on the similar effective ionic radii and charge balance, the Tm 3+ , Tb 3+ , Dy 3+ and Eu 3+ ions are expected to occupy Gd 3+ sites in LiGd(WO 4 ) 2 .…”
Section: Phase Identication and Structurementioning
confidence: 99%
“…The multicolor tuning of phosphors has been achieved by co-doping RE 3+ ion into suitable host lattice, such as Eu 3+ -Bi 3+ , 20 Tm 3+ -Dy 3+ (ref. 21) and Tb 3+ -Eu 3+ . [22][23][24] It has been reported that Na 3 La(PO 4 ) 2 crystallizes in the orthorhombic structure.…”
Section: Introductionmentioning
confidence: 95%
“…As a result, numerous efforts have recently been made to develop the single-phase white-light-emitting phosphors based on the mechanism of energy transfer from sensitizer to activator, such as Ce 3+ /Mn 2+ , Eu 2+ /Mn 2+ , Ce 3+ /Eu 2+ , Tm 3+ /Dy 3+ etc. [11][12][13][14][15][16] Note that the above examples based on energy transfer to obtain white light are realized by co-doping various luminescent ions into one host. However, some hosts, such as niobate, vanadate and tungstate, themselves contain luminescent centers that can generate broad ultraviolet-visible emissions and effectively transfer their energy to an activator ion.…”
Section: Introductionmentioning
confidence: 99%